EVALUACIÓN FINANCIERA A LA COMPAÑÍA ALIMENTOS & BEBIDAS DEL SUR INDUIWIA AGROINDUSTRIA PERÍODO 2017 - López Robles, Priscila Monserrat (2019)
This dissertation document named “FINANCIAL EVALUATION TO THE COMPANY FOOD & BEVERAGES OF THE SOUTH INDUIWIA AGROINDUSTRIA PERIOD 2017" was carried out to comply as part of the requirements to obtain the Accounting and Audit Engineer public Accountant Auditor degree, also with the purpose to publicise the financial-economic development of the company in the period indicated and subsequently to a good and appropriate decision making that leads to the proper functioning of it. The methodology applied for its execution consisted of gathering reliable and trustworthy information from the company's manager and accountant, in order to apply the procedures of the financial evaluation and determine its liquidity, indebtedness, profitability and activity situation that it has in 2017, to be able to propose strategies for the improvement of the company. Then it was carried out based on the goals set, for which proceeded to apply and interpret financial indicators of liquidity, activity, indebtedness, profitability, cost benefit, equilibrium point, net present value, internal rate of return and recovery period in where critical points for decision making were - 5 - established, determining that the company has a high percentage of indebtedness and a little significant profitability for the 2017 period. Subsequently, decision strategies were proposed to guide the company's management in making decisions to improve liquidity, collections, and above all, profitability. Finally, a Financial Evaluation report is prepared, which contains the conclusions and recommendations that will serve as a financial guide to shareholders for better decision making in the company.